Digital watermarking for medical image authentication - Noor Aqilah, Abdul Halim (2019)
The influence of digital image in the fields of medical line had become a major impact nowadays. However, with the increasing use of medical image in digital form, so does the potential of the image to be exposed to threat of being modified. Therefore, it is crucial for the medical image to be protected from unauthorized usage. Digital watermarking serves well for this situation. The aim of this research is to propose an improve method for watermarking authentication of medical image. Watermark image will be embedded into the medical image by using fragile watermarking schemes. Afterwards, the watermarked medical image will be tested with various type of threat such as cropping and compression before the watermark is extracted back from the watermarked medical image to inspect its’ authenticity. Reversible Watermarking provides the authentication that can retrieve the original image and the watermark. For this research, fragile watermarking is projected where the method of operation is to let the embedded watermark to be destroyed easily if the watermarked image undergoes even slight modification in order to prove the authenticity of the medical image. This will help in proving authenticity of medical images.